TEACHING READING RECOUNT TEXTS THROUGH EVIDENCE-BASED STRATEGY TO THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 7 OF PALEMBANG - Tahrun Tahrun; Noviati Noviati; Intan Maulidasari (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThe title of this study was teaching reading recount texts through evidence-based strategy to the eighth grade students of State Junior high School 7 of Palembang. The problem of this study was the students have difficulties to identify the meaning of the word, main idea of the texts, and detail information even they enjoyed in reading learning. It makes the students hard to understand the text, especially in reading recount texts. The objective of this study was to find out whether or not there are any significantly difference by the students who are teach recount text through evidence-based strategy and those who are not. The true-experimental method with randomized pre-test and pot-test control group design was used in this study. The data was analyzed through matched t-test and independent t-test. The population of this study was all the eighth grade students of State Junior High School 7 of Palembang Academic Year 2018/2019 with the total number of population was 328 students from 11 classes. The simple cluster sampling used in this study. The samples are VIII.1 as the experimental group with 31 students and VIII.5 as the control group with 28 students. The average score of post-test in experimental group was 85,56 and the average score in the post-test in control group was 79,73. based on the findings in this study, the researcher was concluded that there was significant difference of students’ score between the students who were taught through evidence-based strategy and those who were taught without evidence-based strategy in reading recount texts at State Junior High School 7 of Palembang. It could be seen from the value of t-obtained was higher than the value of t-table (2,78>1,697). It means that Ho was rejected and Ha was accepted. Form the data analysis above, it could be conclude that there was significant difference in reading recount texts of the eighth grade students of State Junior High School 7 of Palembang who were taught through evidence-based strategy and those who were not.Keyword: Reading, Recount Texts, and Evidence-based strategy